Commentary: If Education Is the Key to Reconciliation, How Will Professional Development Contribute to Unlocking the Process? (LEARNing Landscapes, 2015)
This text considers the urgency of teacher learning, given the recent culmination of Canada’s six-year Truth and Reconciliation Commission (TRC) and in light of the position taken by the TRC that, "Education holds the key to reconciliation." Beginning with a reflection on the author’s formative encounters as a practitioner, the text goes on to question how teachers will be prepared for the significant role they have been called on to play. The latter section takes into account that professional learning is emotional and cerebral, and points to the need for emotional readiness among teachers participating in reconciliation practices with students.
Keywords: Truth and Reconciliation Commission (TRC); teacher learning; reflection; emotional readiness; professional learning